THE IMPACT OF CORONAVIRUS OUTBREAK ON INDONESIA’S TOURISM SECTOR - Santoso, Dwi Priyo (Universitas Nusantara PGRI Kediri, 2020)
The world is being shaken by the case of spreading coronavirus outbreak (COVID-19) which is increasingly spreading and expanding rapidly and becoming the largest global polemic at present. The Covid-19 pandemic caused disruptions to global, domestic supply chains, financial market volatility, shocks to consumer demand, and negative impacts on key sectors such as travel and tourism. Indonesia is also one of the countries that face a big impact on the tourism sector. This study used a desk research method with data and information collected through data inspection and analysis that use secondary data, either in the form of company internal/external documents, legislation, reports, statistic data, and bibliography study to obtain the information of Coronavirus Outbreak Impacts on Indonesia’s Tourism Sector. Badan Pusat Statistik (BPS) recorded that in January to June 2020, the number of foreign tourists visiting to Indonesia reached 3.09 million visits, or decreased 59.96 percent compared to the number of foreign tourists visiting in the previous year, which totaled 7.72 million visits. It affects the national tourism foreign exchange that fell by 97 percent from USD 119 million to only USD 30 million. To face this situation, Kemenparekraf (Ministry of Tourism) has provided tax subsidies to parties involved in the tourism sector.